Purification and Analysis of the CREPT Antibody from Mouse Ascites - Zhihao Xie; Jun Li; Xinbao Hao; Lu Xu (Applied Bionics and Biomechanics)
Background and objective. The cell cycle-related and expression-elevated protein in tumor (CREPT) is overexpressed in several human cancers. Establishing a method for purifying CREPT from mouse ascites is vital for further research. This study was aimed at establishing a method for purifying CREPT from mouse ascites. Methods. Cells were cultivated properly to obtain 3E10 CREPT monoclonal antibody cells in the logarithmic growth stage. Monoclonal antibody cells were injected into the abdominal cavity of sensitized mice. The flowing ascites were observed for 7-15 days. The antibody protein was obtained by collection, filtration, dilution, loading, and chromatography. Furthermore, its binding force was detected by SDS-PAGE and Western blot techniques. Results. The antibody protein was successfully obtained with a purity of 1895 μg/mL with high liveness. Conclusion. This study establishes a one-step purification method for obtaining monoclonal antibody with high liveness and purity for CREPT ascites antibody. This method is simple to perform and lays a foundation for the preparation and purification of humanized monoclonal antibodies in the future. In addition, it provides a basis for further research to investigate how CREPT affects the occurrence and development of different tumors.